TRANSFORMASI BISNIS DIGITAL: MEMBERDAYAKAN SISWA SEKOLAH MENENGAH ATAS DENGAN PELUANG WIRAUSAHA EKONOMI DIGITAL - Rahmani, Zikri; Putra, Agung Rizki; Hamsani, Hamsani; S., M. Afdal (Jurnal Abdi Insani, 2024)
In today's technological era, there are many entrepreneurial opportunities for the community, one of which is Digital Business entrepreneurship. Technological developments not only make it easier for people to interact, but also make it easier for people to do business. digital business can be done by anyone, including students as generation Z who are literate in technological developments. However, most of generation Z do not know how to start or look for entrepreneurial opportunities in the digital era. This community service aims to encourage and develop an entrepreneurial spirit for high school students with digital economy entrepreneurial opportunities that students can do without disrupting their learning process at school. The implementation of this activity is carried out by providing training/workshops to increase students' awareness of the many business opportunities in the digital world that they can do, starting from the introduction of entrepreneurship, business opportunities, and good business plans as well as practice (simulation) of making a business. The results of community service activities are providing education and understanding of the application of digital economy business opportunities for SMAN 4 Kota Pangkal Pinang students such as developing digital businesses, developing digital products, business management, and digital marketing. The conclusion of this service is to increase knowledge and make students aware of the many digital business opportunities they can do without having to interfere with the learning process for students.